Cardiac lipoblastoma of the pulmonary valve: A rare tumor in an unusual location. Issue 7 (24th April 2021) - Feng, Tong; Zhangke, Guo; Song, Bai
Abstract: Backgroud: Lipoblastoma is a rare, benign, fatty tissue tumour tumor that occurs in infancy and early childhood. Intrathoracic and mediastinal involvement of this tumour is rare, and an intracardiac location is even rarer. Aims: To report the first case of a lipoblastoma in the pulmonary valve. Materials: In this study, we report the case of a 15‐month‐old girl who presented with a tumour in the pulmonary valve. Results: The tumour was completely resected macroscopically. Histological examination of the lesion confirmed the diagnosis of lipoblastoma. Discussion: Most primary cardiac tumours are benign in the sense they are not invasive. However, benign tumours maintain the potential for serious illness related to significant haemodynamic compromise or life‐threatening dysrhythmias. Due to the association of lipoblastoma with other heart malformations, preoperative diagnosis remains challenging. Conclusion: Tumours on the heart valve are more likely to cause haemodynamic disturbances. Complete resection yields an excellent prognosis.